Pengaruh Edukasi Managemen Nyeri Non-Farmakologi Desminore terhadap Pengetahuan Remaja Putri di SMP Nurul Jadid - Kholisotin, Kholisotin; Helmawati, Helmawati; Jennah, Miftahul; Siami, Holisatus (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2021)
Menstruation can cause disturbances that can be related to changes in the length of the menstrual cycle, the amount of blood that comes out during menstruation, and other menstrual disorders. The most common disorder is dysmenorrhea. Health education is needed to provide information that can affect the knowledge of young women so that adolescents who experience dysmenorrhea can handle it well. The purpose of this study was to determine the effect of Non-Pharmacological Pain Management Education on Dysmenorrhea on Adolescent Girls' Knowledge at Junior high school Nurul Jadid. This research design uses a Quasy-Experimental approach with a Prettest-Posttest research design with a control group. Data were collected using a questionnaire with a total sample of 30 in the intervention group and 30 in the control group using a total sampling technique. The results of the Wilcoxon analysis of students' knowledge levels showed that there was a significant difference between the prettest and posttest in the intervention group (p= Sig 0.000), the results of the Wilcoxon analysis showed no significant difference in the level of knowledge of students in the control group (p=1,000). The Mann-Whitney analysis showed that there was a significant difference in the posttest student knowledge level between the two groups with a p-value of 0.001 (<0.05). Conclusion: Non-pharmacological pain management education for dysmenorrhea has an effect on increasing knowledge in adolescent girls at Mts Nurul Jadid. The results of the study are expected to provide input in the development of health promotion, especially reproductive health education for female adolescents.